Learning, Teaching and First Aid in times of COVID-19 (International Journal of First Aid Education)
Following precautionary measures set forth by the WHO upon declaring the COVID-19 outbreak a pandemic, the shutting down of first aid training courses, continuous first aid education and other face to face training has had the effect of disabling first aid educators to appropriately train millions of volunteers how to deal with COVID-19, how to keep them, their families and their communities safe, and has also limited the sharing of information on appropriate use of personal protection equipment (PPE). The editorial cites among other factors the disparities in opportunities for schooling and online education between the wealthy and poor, stressing that shifting to online first aid education is not happening in a vacuum and is not only about changing the tools and platforms (as challenging as they might be), but also about adapting what is already available to take account of the developing situation, alterations in population needs and adapting to first aid learning in diverse settings where many of those differences are not known or obvious to us.